Desain dan Pembuatan Mesin CNC Milling untuk Pembuatan Ukiran Kerajinan Kayu - Sunarto, Sunarto; Hartono, Hartono; Carli, Carli; Daryadi, Daryadi; Tjahjono, Bambang; Setiyawan, Trio (Mechanical Engineering Department - Semarang State Polytechnic, 2022)
The furniture industry is an industry that processes raw materials or semi-finished materials from wood, rattan and other natural raw materials into finished products that are ready for use and have higher added value. There are many furniture industries spread across Indonesia, with quite large centers located in Jepara, Sukoharjo, Surakarta, Klaten, and others. Along with the development of industrial technology, making work becomes more efficient and easier. Therefore, it is necessary to apply technology in the industrial world in Indonesia, especially in the furniture industry. The current technology commonly applied to the furniture industry is the CNC milling machine. The use of this CNC machine aims to solve problems in the production of wood carving crafts or furniture, such as mass products that cannot be the same and product processing time that cannot be ascertained. Besides, the use of this CNC machine can reduce cycle times and increase the work efficiency of the furniture industry. Based on this information, we had the idea to make this CNC milling machine to support the progress of the Indonesian furniture industry. During the manufacturing of this CNC machine, we carried out theoretical research and field surveys. The research stages we carried out were identification of needs, problem formulation, synthesis, analysis, evaluation and presentation. Based on these results, it was found that the workable raw material had a maximum dimension of 40 × 40 [cm], a maximum feed rate of 192 [mm/min], a maximum spindle rotating speed of 12,000 [rpm] and a cutting velocity of 75.4 [m/min].